HIV-Exposed Uninfected Infants in Zimbabwe: Insights into Health Outcomes in the Pre-Antiretroviral Therapy Era - Evans, Ceri; Humphrey, Jean H.; Ntozini, Robert; Prendergast, Andrew J. (Frontiers in Immunology, 2016)
The ZVITAMBO trial recruited 14110 mother-infant pairs to a randomised controlled trial of vitamin A between 1997-2000, before the availability of antiretroviral therapy for HIV prophylaxis or treatment in Zimbabwe. The HIV status of mothers and infants was well characterised through 1-2 years of follow-up, leading to the largest cohort to date of HIV-exposed uninfected (HEU) infants (n=3135), with a suitable comparison group of HIV-unexposed infants (n=9510). Here, we draw on 10 years of published findings from the ZVITAMBO trial. HEU infants had increased morbidity compared to HIV-unexposed infants, with 50% more hospitalisations in the neonatal period and 30% more sick clinic visits during infancy, particularly for skin infections, lower respiratory tract infections and oral thrush. HEU children had 3.9-fold and 2.0-fold higher mortality than HIV-unexposed children during the first and second years of life, respectively, most commonly due to acute respiratory infections, diarrhoea/dysentery, malnutrition, sepsis and meningitis. Infant morbidity and mortality was strongly related to maternal HIV disease severity, with a risk that remained until maternal CD4 counts were >800 cells/uL. HEU infants were more likely to be premature and small-for-gestational age than HIV-unexposed infants, and had more postnatal growth failure. Here, we propose a conceptual framework to explain the increased risk of infectious morbidity, mortality and growth failure among HEU infants, hypothesizing that immune activation and inflammation are key drivers of both infection susceptibility and growth failure. Future studies should further dissect the causes of infection susceptibility and growth failure, and determine the impact of ART and co-trimoxazole on outcomes of this vulnerable group of infants in the current era.